Labour, diaspora and marginality : Essays in honour of Professor Sabyasachi Bhattacharya - Rao, Yagati Chinna; Patel, Hitender K. (Delhi : Primus Books, 2024)
Labour, Diaspora and Marginality traces the intellectual legacy of Professor Sabyasachi Bhattacharya (1938-2019), a towering figure in the field of Indian history. He was an exceptional intellectual, infused with ethical sensibility and humanism. Beginning with his earlier forte in economic history, he eventually contributed to a significant trend in labour studies and gave shape to that turn within the specific context of India and other postcolonial nations. He left an indelible impression across the sub-_elds within history such as education, and political, socio-cultural and intellectual histories of India.
Keywords: Dalits -- History -- India; India -- History; Labor -- History -- India